HUBUNGAN ANTARA STATUS GIZI DENGAN TUMBUH KEMBANG ANAK USIA 1-3 TAHUN (TOODLER) DI PUSKESMAS SEMULA JADI KOTA TANJUNGBALAI TAHUN 2019 - ROSTINA AFRIDA POHAN (JURNAL ILMIAH KOHESI, 2021)
This study aims to find out the relationship between nutritional status and the growth of children aged 1-3 years (toodler).This research method uses correlation design with cross sectional approach. This study was conducted in PuskesmasSemula Jadi against 40 children aged 1-3 years who were taken using purposive sampling techniques by paying attention toinclusion criteria. The measuring instrument used is an observation table to look at the nutritional status of children whoperpedoman on 10 criteria of well-nourished children and DDST table to measure child development, as well asdemographic characteristics sheet to see the characteristics of respondents.. The analysis used is univariate and bivariateanalysis with chi-square test. The results showed that there is a meaningful relationship between nutritional status and thegrowth of children aged 1-3 years (p-value= 0.000; α = 0.05). Based on the results of this study is expected for healthworkers to socialize, measurement of growth with DDST, in order to detect developmental delays in children immediately.